GARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING ( Studi Penjualan Produk Sampingan / By Product pada PT. Perkebunan Nusantara V Pekanbaru ) - Syafendra, Rian; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research is motivated by the importance of maintaining customer loyalty in a company because this is a vital part that must be maintained and strived for by the company in supporting its marketing. To maintain and improve it requires good service quality from the company to customers. This will then create a sense of satisfaction from customers so as to make customers loyal and loyal to the company. This research was conducted at PT. Perkebunan Nusantara V, Jl. Rambutan No.43, East Sidomulyo, Kec. Marpoyan Damai, Pekanbaru City, Riau 28289, Indonesia. The purpose of this study was to determine and analyze the effect of service quality on customer loyalty through consumer satisfaction in the sale of PTPN V Pekanbaru products. The sample of this study was taken as many as 50 respondents using the census method. In this research, the method used is descriptive and quantitative analysis. The data obtained from the results of the questionnaire/questionnaire were then tested using the PLS (Partial Least Square) analysis technique through the SmartPLS software. In this study the results obtained are that Service Quality (X) has a positive and significant effect on Customer Loyalty (Y), Service Quality (X) has a positive and significant effect on consumer goals (Z), consumer goals (Z) has a positive and significant impact on consumer goals (Z). Customer Loyalty (Y) and Service Quality (X) have a positive and significant effect on Customer Loyalty (Y) through the Consumer Goals (Z) as Intervening Variables on By-Product sales at PT. Nusantara V Pekanbaru Plantation.Keywords: Service Quality, Customer Loyalty, and Consumer Goals